Press-ekspress . Press-ekspress . Press Express . Пресс-экспресс - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Leonid Filatov's speech on the media and famous people; discussion on President Boris Yeltsin's address to the nation on 20 March 1993; article in the newspaper "Trud" on "misguided" people who want to work abroad; the tabloid newspaper "Cranberry." Featured in the program: Filatov, Leonid Alekseevich (Director) Contributors: Egorshev, Andrei (Anchor) Series description: Press reviews, interviews with journalists, presentations of magazines and newspapers. Монолог Леонида Филатова о прессе и известных людях; обсуждение обращения президента Бориса Ельцина к народу от 20 марта 1993 года; статья в газете "Труд" об обманутых людях, которые желали работать за границей; бульварная газета "Клюква.". В программе участвуют: Филатов, Леонид Алексеевич (Режиссер) Создатели: Егоршев, Андрей (Ведущий/Ведущая) Описание серии: Обзор прессы, интервью с журналистами, представление журналов и газет.